Real-time remote monitoring system for aquaculture water quality - Hongpin, Luo; Guanglin, Li; Weifeng, Peng; Jie, Song; Qiuwei, Bai (International Journal of Agricultural and Biological Engineering, 2015)
A multi-parameters monitoring system based on wireless network was set up to achieve remote real-time monitoring of aquaculture water quality, in order to improve the quality of aquaculture products and solve such problems as being difficult in wiring and high costs in current monitoring system. In the system solar cells and lithium cells were used for power supply. The YCS-2000 dissolved oxygen sensor, pH electrode, Pt1000 temperature sensor and ammonia nitrogen sensor were used to monitor the parameters of aquaculture water quality; STM32F103 chip was used for data processing; Zigbee and GPRS modules were used for data transmission to the remote monitoring center, where the data were stored and displayed. The system was connected with aerator to realize automatic control of dissolved oxygen concentration. The test results showed high confidence level of data transmission with a packet loss rate of 0.43%. Therefore, the system could fulfill the real-time remote monitoring of aquaculture water quality and had great practical significance in reduction of labor intensity, improvement of quality of aquatic products and protection of water environment. Keywords: aquaculture, water quality, real-time monitoring, wireless sensor network, aerator DOI: 10.3965/j.ijabe.20150806.1486 Citation: Luo H P, Li G L, Peng W F, Song J, Bai Q W. Real-time remote monitoring system for aquaculture water quality. Int J Agric & Biol Eng, 2015; 8(6): 136－143.